2014
DOI: 10.3343/alm.2014.34.1.31
|View full text |Cite
|
Sign up to set email alerts
|

The Drug Resistance Profile of Mycobacterium abscessus Group Strains from Korea

Abstract: BackgroundBacteria of the Mycobacterium abscessus group are the second most common pathogens responsible for lung disease caused by nontuberculous mycobacteria in Korea. There is still a lack of studies investigating the genetic mechanisms involved in M. abscessus resistance to antibiotics other than clarithromycin. This study investigated the characteristics of drug resistance exhibited by M. abscessus clinical isolates from Korea.MethodsWe performed drug susceptibility testing for a total of 404 M. abscessus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 26 publications
1
36
1
1
Order By: Relevance
“…Clarithromycin is a very important drug in the treatment of these infections; however, several countries have reported the occurrence of induced resistance. Therefore, it is necessary to conduct a clarithromycin susceptibility testing so that a physician can choose the best regimen for the patient …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clarithromycin is a very important drug in the treatment of these infections; however, several countries have reported the occurrence of induced resistance. Therefore, it is necessary to conduct a clarithromycin susceptibility testing so that a physician can choose the best regimen for the patient …”
Section: Discussionmentioning
confidence: 99%
“…Clarithromycin is a very important drug in the treatment of these infections; however, several countries have reported the occurrence of induced resistance. Therefore, it is necessary to conduct a clarithromycin susceptibility testing so that a physician can choose the best regimen for the patient (8,9,(22)(23)(24) In this study, MIC was performed according to the CLSI recommendation and with extended incubation to identify a possible induced resistance. This type of resistance can solely be detected when there is an extended incubation period, as it is expressed in the presence of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Smooth colonies of M. abscessus and M. massiliense were moist, shiny, and round, while the rough colonies were dry, waxier, and wrinkled. The smooth colony of M. abscessus complex expresses glycopeptidolipid (GPL) on its cell wall and forms biofilms, while rough colony of M. abscessus complex does not form biofilms due to minimal amounts of GPL (Howard et al ., 2006; Byrd & Lyons, 1999). Moreover, rough colony of M. abscessus is associated with virulence compared to the smooth colony of M. abscessus .…”
Section: Resultsmentioning
confidence: 99%
“…A region of the rrl gene which encodes the peptidyltransferase domain of the 23S rRNA is associated with clarithromycin point mutations at positions A2058 and A2059. In addition, the erm gene is also involved in inducible resistance to clarithromycin (10). Bedaquiline is an ATP synthesis inhibitor that inhibits AtpE (mycobacterial ATP synthase), an essential enzyme in mycobacterial energy metabolism.…”
Section: Lcb01-0371 Is Effective Against M Abscessusmentioning
confidence: 99%
“…The expressed enzymes, such as rifampin ADP-ribosyltransferase, as well as a monooxygenase, may be involved in its resistance to rifampin (7). Recently, researchers also have observed that M. abscessus expresses the inducible erythromycin ribosome methyltransferase (erm) gene after treatment with a macrolide, which results in a poor response to clarithromycin and erythromycin (10). M. abscessus has already acquired antibiotic resistance via the spontaneous mutation of critical targets of antibiotics, rather than through horizontal transmission.…”
mentioning
confidence: 99%